(3GdEYaGAGJ ef VQjHI GdONd (B/s - (3GdLMjTj, YHO GdHGSW Ydj LGSes ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2008)
(3jVe GdJYQja HGdVQjHI Ydi GdONd, GdEYaGAGJ dCSHGH ELJeGYjI, GdEYaGAGJ dCSHGH GbJUGOjI hdEYJHGQGJ OhdjI , GdEYaGAGJ defY GdEROhGL GdVQjHjs
(3GdeQGLY U(B.155s
Keywords: (3GdVQGFHs; (3VQGFH GdONds